Peningkatan Aktivitas dan Prestasi Belajar Materi Creating Captions dengan Metode Quantum Teaching - Rohmat Mutiah (MADRASCIENCE: Jurnal Pendidikan Islam, Sains, Sosial, dan Budaya, 2022)
The findings of observations of students in class XII MIPA 1 MAN 1 Ciamis show that they are less engaged in class activities for learning. Less than ideal learning outcomes are a result of this. The purpose of this study is to ascertain whether class XII MIPA 1 Madrasah Aliyah Negeri (MAN) 1 Ciamis students are becoming more active and learning more on the topic of caption creation using the Quantum Teaching approach. This resrarch was employed Classroom action research as the methodology that conducted in two cycles. The results of students’ achievement in the learning process before using the Quantum Teaching method obtained an average value of 62,71. When the teacher uses the Quantum Teaching method in the first cycle, the average score of students is 73,55. In the second cycle, the average results showed that students' activities in learning activities before using Quantum Teaching obtained an average score of 64.55, then increased to 74.71 in the first cycle and in the second cycle, 86.71 from the ideal score of 100. In the second cycle, the achievement score was already at the value of the Minimum Competence Criteria (KKM). Value becomes 85.55, from an ideal score of 100. These results indicate that the Quantum Teaching method can improve students’ activity and achievement.